An Environmental Analysis of Live Streaming in Social Media Commerce for Beauty Industry in Indonesia - Rizkia Ayu Amalia; Atik Aprianingsih (International Journal of Business Studies, 2023)
Livestreaming is becoming one of the promotion strategies that companies used to promote the products in this advanced technology development. One of the industry that actively promote the products through live streaming is Beauty Industry. The beauty industry often used few platforms to do the livestreaming, for instance social media. The purpose of this study is to understand that live streaming is becoming one of the digital marketing strategy for beauty industry that has impacted to the industry and also to discuss the underlying potential and understand the weaknesses to avoid in the future. To achieve these goals, data must be collected and then analysed. This research uses a descriptive qualitative method and the data obtained will be analyzed using the SWOT matrix (Strengths, Weaknesses, Opportunities, Threats). The output of this research is expected to be adapted by sellers who utilize video streaming as one of the digital marketing and this research focused on two social commerce platforms, Tiktok & Instagram.